Diversity and the Division of Cognitive Labor. Issue 2 (18th January 2013) - Muldoon, Ryan
Abstract In epistemology and the philosophy of science, there has been an increasing interest in the social aspects of belief acquisition. In particular, there has been a focus on the division of cognitive labor in science. This essay explores several different models of the division of cognitive labor, with particular focus on Kitcher, Strevens, Weisberg and Muldoon, and Zollman. The essay then shows how many of the benefits of the division of cognitive labor flow from leveraging agent diversity. The essay concludes by examining the benefits and burdens of diversity, particularly in the evaluative diversity that can be found in interdisicplinary science.